(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The analysis carried out in this project highlights the concepts, working, advantages and practical applications of programmable logic controllers, along with a comparison with other control systems for industrial automation in repetitive nature of work. This operation is generally used for repetitive nature of work. The main objective of the project is to design a programmable sequential switching of any load using embedded system based PLC concept. The development of this application requires the configuration of PLC architecture - that is, the selection of the machines, and writing debugging of the application program. In this project, the clock plays an important role, wherein it is used in these modes: the set mode, auto mode and manual mode for controlling different industrial loads (bulbs, fans, motors etc.).